Adult Education and Lifelong Learning. The case of GSAE (General Secretary for Adult Education) in Greece - Kalogiannakis, Michail; Vassilakis, Kostas; Alafodimos, Constantinos; Papadakis, Stamatis; Papachristos, Dimitris; Zafeiri, Evi (International Journal of Advanced Corporate Learning (iJAC), 2009)
The participation rates in adult education in Greece are low in comparison with other European countries. Within the framework of the present research an effort has been undertaken in order to evaluate the program of training instructors of adults through distance learning education hosted by the GSAE (General Secretary for Adult Education) and the ICAE (Institute for the Continuing Adult Education) in Greece. Among the most important outcomes of this research was considered to be the positive attitude of the participants concerning the program in general as well as the electronic educational material distributed. Furthermore, the hybrid educational process selected for use by the program was thought to be particularly flexible. As for the programâ??s negative aspects, the main problems noted were the distance certain trainees had to cover in order to participate physically during the scheduled meetings, as well as the technical issues arose within the e-learning environment.